Psychometric properties, factor structure, and German population norms of the multidimensional fatigue inventory (MFI-20) - Westenberger, Adrian; Nöhre, Mariel; Brähler, Elmar; Morfeld, Matthias; de Zwaan, Martina (Frontiers in Psychiatry, 2022)
Objective: The Multidimensional Fatigue Inventory (MFI-20) is commonly used, but its factor structure remains unclear. The MFI-20 consists of five subscales (General fatigue, Physical fatigue, Reduced activity, Reduced motivation, and Mental fatigue). This study investigates the psychometric properties, including the factor structure, in a general German population sample, and tests group hypotheses on gender and age. Another objective is to provide normative data, by gender and age groups. Methods: Using data from a representative German sample (n=2509), reliability and convergent validity measures, group hypothesis testing, and confirmatory/exploratory factor analyses were conducted. Results: The MFI-20 demonstrated satisfactory internal consistency and showed adequate convergent validity with the SF-36. All subscales of the MFI-20 were significantly correlated (.71-.85). Physical fatigue exhibited the highest (.42) and Mental fatigue the lowest (.19) correlation with age. Fatigue scores were significantly higher for females and significantly increasing with age. A five-factor structure showed poor model fit; using an exploratory factor analysis, a two-factor structure emerged (General factor and mental/motivational factor). Conclusions: The MFI-20 is a reliable and valid instrument for measuring fatigue in the general population, but the five-factor structure is not supported. The subscale General fatigue or the MFI-20 total score might measure fatigue sufficiently. The provided norms can be used for further research and individual assessment.